2022
DOI: 10.1038/s41598-022-17344-3
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes in the macular and parafoveal areas of multiple sclerosis patients without optic neuritis

Abstract: Retinal imaging has been proposed as a biomarker for neurological diseases such as multiple sclerosis (MS). Recently, a technique for non-invasive assessment of the retinal microvasculature called optical coherence tomography angiography (OCTA) was introduced. We investigated retinal microvasculature alterations in participants with relapsing–remitting MS (RRMS) without history of optic neuritis (ON) and compared them to a healthy control group. The study was performed in a prospective, case–control design, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…The reason for these conflicting results may be partially due to the failure to account for important biological confounding factors, that is, age, 14 systemic vascular risks (diabetes 15 and systemic hypertension 16 ), signal strength of scans, 17 and/or axial length measurements 18,19 . After accounting for these factors, we found a higher capillary density in the SCP and lower capillary density in the DCP in MSNON subjects as compared to controls 4,20 …”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The reason for these conflicting results may be partially due to the failure to account for important biological confounding factors, that is, age, 14 systemic vascular risks (diabetes 15 and systemic hypertension 16 ), signal strength of scans, 17 and/or axial length measurements 18,19 . After accounting for these factors, we found a higher capillary density in the SCP and lower capillary density in the DCP in MSNON subjects as compared to controls 4,20 …”
Section: Introductionmentioning
confidence: 85%
“…Pupils were not dilated prior to imaging; instead, room lighting was dimmed to achieve maximal pupil dilation. Each participant received two OCT scans, one centered on the macula (512 A‐scans x 128 B‐scans; 6×6 mm) and the other centered on the optic disc (200 A‐scans x 200 B‐scans; 6×6 mm), and one 3×3 mm macula‐centered OCTA scan, with each scan consisting of an isotropic sampling (245×245 pixels) and four consecutive B‐scans obtained at each raster location to compute the angiographic information using an optical microangiography protocol 4,20 . The quality of scans was reviewed by a single trained grader masked to the participant's characteristics according to APOSTEL recommendations and the OSCAR‐IB protocol 24–26 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these authors did not find any vascular density damage in MS patients without ON [ 10 , 11 ]. More recently, Bostan et al found an impairment of perifoveolar vascular density in MS patients without ON [ 12 ].…”
Section: Introductionmentioning
confidence: 99%